On Our Selection - Rudd, Steele, 1868-1935 (Salt Lake City, UT : Project Gutenberg, 2003)
"On Our Selection" by Steele Rudd is a collection of stories published in 1899. Set in the Australian bush, these sketches follow the Rudd family$1 (Bincluding the memorable Dad and Dave$1 (Bas they struggle to establish a farm on crown land. Through hardships, small triumphs, and daily challenges, the stories capture the lives of pioneering selectors facing poverty, conflict with squatters, and the unforgiving realities of rural life. This truthful portrayal of Australian settler experience became wildly popular, selling over 250,000 copies and inspiring numerous stage and film adaptations. (This is an automatically generated summary.)s
Wikipedia page about this book: https://en.wikipedia.org/wiki/On_Our_Selection
Release date is 2003-01-01
Produced by Col Choat. HTML version by Al Haines.
Keywords: Australia -- Fiction; Rural families -- Fiction; Farm life -- Fiction; Australia -- Social life and customs -- Fiction; Humorous stories, Australian